Sergentomyia schwetzi: Salivary gland transcriptome, proteome and enzymatic activities in two lineages adapted to different blood sources - Polanska, Nikola; Ishemgulova, Aygul; Volfova, Vera; Flegontov, Pavel; Votypka, Jan; Yurchenko, Vyacheslav; Volf, Petr (PloS one, 2020)
During the blood feeding, sand fly females inject saliva containing immunomodulatory and anti-haemostatic molecules into their vertebrate hosts. The saliva composition is species-specific, likely due to an adaptation to particular haemostatic pathways of their preferred host. Research on sand fly saliva is limited to the representatives of two best-studied genera, Phlebotomus and Lutzomyia. Although the members of the genus Sergentomyia are highly abundant in many areas in the Old World, their role in human disease transmission remains uncertain. Most Sergentomyia spp. preferentially attack various species of reptiles, but feeding on warm-blooded vertebrates, including humans and domestic animals, has been repeatedly described, especially for Sergentomyia schwetzi, of which salivary gland transcriptome and proteome is analyzed in the current study. Illumina RNA sequencing and de novo assembly of the reads and their annotation revealed 17,293 sequences homologous to other arthropods' proteins. In the sialome, all proteins typical for sand fly saliva were identified-antigen 5-related, lufaxin, yellow-related, PpSP15-like, D7-related, ParSP25-like, and silk proteins, as well as less frequent salivary proteins included 71kDa-like, ParSP80-like, SP16-like, and ParSP17-like proteins. Salivary enzymes include apyrase, hyaluronidase, endonuclease, amylase, lipase A2, adenosine deaminase, pyrophosphatase, 5'nucleotidase, and ribonuclease. Proteomics analysis of salivary glands identified 631 proteins, 81 of which are likely secreted into the saliva. We also compared two S. schwetzi lineages derived from the same origin. These lineages were adapted for over 40 generations for blood feeding either on mice (S-M) or geckos (S-G), two vertebrate hosts with different haemostatic mechanisms. Altogether, 20 and 40 annotated salivary transcripts were up-regulated in the S-M and S-G lineage, respectively. Proteomic comparison revealed ten salivary proteins more abundant in the lineage S-M, whereas 66 salivary proteins were enriched in the lineage S-G. No difference between lineages was found for apyrase activity; contrarily the hyaluronidase activity was significantly higher in the lineage feeding on mice.
Keywords: Receptors, Odorant; apyrasa; Lizards; Psychodidae; Hyaluronoglucosaminidase; transkriptom; ještěři; Mice; Salivary Glands; hyaluronoglukosaminidasa; Transcriptome; Apyrase; receptory pachové; zvířata; hmyzí proteiny; fylogeneze; slinné žlázy; myši; Insect Proteins; Phylogeny; Animals